Relevant aspects for the development of a knowledge management program for public administration - Ripoli, Simone Cristina Ceron [UNESP]; Martello, Marcelo Ricardo [UNESP]; Bussadori, Meiriellen Cristina Faria [UNESP] (Univ Federal Parana, Dept Ciencia & Gestao Informacao, 2022)
Introduction: this study sought to address the characteristics and specific techniques to be observed in the construction of a knowledge management model in public administration. Knowledge and information are indispensable elements for the survival of both public and private organizations. Despite this common aspect, knowledge management models must be developed specifically for the type of organization where they will be used. Method: the main differences between public and private organizations that justify the use of a model built specifically for public administration were identified. Bibliographies of reference authors in the subject of knowledge management and in the area of public administration were used. As for its objectives, the research is exploratory with the realization of bibliographic survey.Results: the results show that the most used model in Brazilian public administration observes all the specificities of public administration and adopts the techniques and specific characteristics in knowledge management in public administration. Conclusions: once the organizational environment where the knowledge management model will be applied is not observed, it tends to be born towards failure. The lack of knowledge of the peculiarities of public administration implies in the failure in the implementation of programs, which despite having their successful application in private organizations, do not prosper in the public sphere.
Keywords: Knowledge management; Public administration; Information; Public organizations